ANALISIS STRUKTUR WACANA DAN KESALAHAN BERBAHASA TEKS ULASAN BUKU FIKSI SISWA SEKOLAH MENENGAH ATAS - Rahmawati, Halimah Nina; Setiawan, Budhi; Suryanto, Edy (Basastra: Jurnal Bahasa, Sastra, dan Pengajarannya, 2020)
This study aims to explain the errors of discourse structure and mistake in Indonesian language text review fiction book grade XI students of Muhammadiyah 1 Karanganyar High School. This study describes the causes of errors and the efforts teachers can make to minimize further errors. This research is a case study with research data in the form of discourse structure and language errors in the text of fiction book reviews by student. Data collection technique s were carried out by means of observation, competency tests, and interviews. Validity test used triangulation of data source and theory triangulation. Data analysis techniques using content analysis. The result of the study found: (1) discourse structure errors, namely 20 errors in the review text title, 17 closing errors, 12 content errors, and 11 preliminary errors, (2) language errors include 174 uppercase mistakes, 60 comma punctuation errors, 36 dot punctuation errors, 18 preposition errors, 10 italic errors, 4 colon errors, 3 hyphen errors, 3 repeat words errors, 3 particle errors, 2 semicolon errors, 95 errors diction, sentences, and paragraphs; the absence of spelling and punctuation material on the syllabus, lack of student motivation, and the influence of foreign languages and regional languages; (4) efforts to reduce language errors, namely integrating the material, providing motivation to students, and increasing mastery of the correct linguistic rules